The Moderating Role of the Hostile-World Scenario in the Connections Between COVID-19 Worries, Loneliness, and Anxiety - Yoav S. Bergman; Amit Shrira; Yuval Palgi; Dov Shmotkin (Frontiers in Psychology, 2021)
The COVID-19 pandemic has had pronounced effects on individuals' psychological well-being around the world. Concerns regarding the consequences of infection, as well as the general uncertainty and governmental regulations have resulted in increased psychological distress among many populations and cultures. In this regard, research has shown that the manner by which individuals perceive such large-scale threats and appraise them significantly contributes to the psychological consequences of such events. According to the Hostile-World Scenario (HWS) model, negative engagement (NE) with such threats weakens one's competence and coping abilities, whereas positive engagement (PE) facilitates resilience and enhances psychological adjustment. Accordingly, the current study examines the moderating role of both NE and PE in the connections of two main features of the current pandemic, COVID-19-related worries and loneliness, with anxiety. Data were collected between March 16 and April 14, 2020, from 1,112 Israelis (age range 17–92, M = 46.90, SD = 16.46), who provided information regarding COVID-19 health worries, loneliness, and anxiety. A special measure assembled items pertinent to the HWS-NE and HWS-PE throughout the survey. Results demonstrated that both HWS-NE and HWS-PE were significant moderators. COVID-19-related health worries/loneliness were linked with anxiety only among individuals with high HWS-NE, and were non-significant among those with low HWS-NE. Moreover, the positive association between loneliness and anxiety was significantly mitigated by high HWS-PE. The discussion highlights the importance of the HWS for understanding the psychological consequences of COVID-19 and offers practical suggestions, which may aid mental health practitioners in providing assistance and support to the general population.